Di-tert-butylchlorido(N,N-dibenzyldithiocarbamato)tin(IV). - Abdul Muthalib, Amirah Faizah; Baba, Ibrahim; Mohamed Tahir, Mohamed Ibrahim; Tiekink, Edward R. T. (International Union of Crystallography, 2011)
The SnIV atom in the title diorganotin dithiocarbamate, [Sn(C4H9)2(C15H14NS2)Cl], is pentacoordinated by an asymmetrically coordinating dithiocarbamate ligand, a Cl atom and two C atoms of the Sn-bound tert-butyl groups. The resulting C2ClS2 donor set defines a coordination geometry intermediate between square pyramidal and trigonal bipyramidal with a slight tendency towards the former.